1992
DOI: 10.3164/jcbn.12.11
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin/GRP Stimulates a Protein Kinase in Swiss 3T3 Cells That Phosphorylates Microtubule-Associated Protein Kinase.

Abstract: SummaryNerve growth factor (NGF)-and epidermal growth factor (EGF)-stimulated MAP kinase activities from PC-12 cells were recently found to be resolvable into two peaks (microtubule-associated protein[MAP] kinases I and II) by ion-exchange or hydrophobic-interaction HPLC, and both kinases I and II were activated by various growth factors, by okadaic acid, and by phorbol esters. In the present study both MAP kinases I and II were also activated by bombesin/gastrin-releasing peptide (GRP) in Swiss 3T3 cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…MAPKs are key components of signaling pathways downstream of a variety of cell surface receptors including tyrosine kinase receptors, integrins, G proteincoupled receptors, and perhaps by as yet not identified shear stress receptors (Miyasaka et al, 1990;Duff et al, 1992;Karin, 1994;Schlaepfer et al, 1994;Morino et al, 1995;Zhu and Assoian, 1995;Arai and Escobedo, 1996;Jo et al, 1997). MAPKs phosphorylate and regulate key intracellular enzymes and transcription factors required for cell cycle progression and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs are key components of signaling pathways downstream of a variety of cell surface receptors including tyrosine kinase receptors, integrins, G proteincoupled receptors, and perhaps by as yet not identified shear stress receptors (Miyasaka et al, 1990;Duff et al, 1992;Karin, 1994;Schlaepfer et al, 1994;Morino et al, 1995;Zhu and Assoian, 1995;Arai and Escobedo, 1996;Jo et al, 1997). MAPKs phosphorylate and regulate key intracellular enzymes and transcription factors required for cell cycle progression and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is good evidence that trk, which is involved in high-affinity NGF binding, acts via a tyrosine kinase pathway (Kaplan et al, 199 1;Nebreda et al, 1991). Furthermore, it has been shown that NGF stimulates the tyrosine phosphorylation of several intracellular proteins including MAP2 kinase 199 l), which itself phosphorylates MAP2 (Landreth et al, 1990;Miyasaka et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The MAP/MBP kinases also have been dubbed extracellular-regulated kinases (ERKs) because they are activated by signals, such as nerve growth factor, that result in differentiation, as well as by signals that result in proliferation (Ray and Sturgill, 1987;Shaw et al, 1988;Rossomando et al, 1989;Ahn et al, 1990;Gotoh et al, 1990b;Miyasaka et al, 1990a;Boulton et al, 1991). There are two well-characterized MAP/MBP kinases of Mr 42 000 and 44 000 that are activated by phosphorylation on threonine and tyrosine ) by a Mr 45 000 protein kinase related to the yeast protein kinases encoded by the byrl and STE7 genes .…”
Section: Introductionmentioning
confidence: 99%